2021
DOI: 10.1021/acs.jpcb.1c07293
|View full text |Cite
|
Sign up to set email alerts
|

O-Methylation in Carbohydrates: An NMR and MD Simulation Study with Application to Methylcellulose

Abstract: Methylated carbohydrates are important from both biological and technical perspectives. Specifically, methylcellulose is an interesting cellulose derivative that has applications in foods, materials, cosmetics, and many other fields. While the molecular dynamics simulation technique has the potential for both advancing the fundamental understanding of this polymer and aiding in the development of specific applications, a general drawback is the lack of experimentally validated interaction potentials for the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 82 publications
0
8
0
Order By: Relevance
“…The anomeric effect provides bolstering stability to α-glycosides due to favorable stereoelectronic and electrostatic interactions . However, due to a competition from the anomeric effect as a result of hyperconjugative lone pair electron delocalization from the endo- and exocyclic oxygen moieties in the case of α-glycosides ( 1-Oxo-α , Figure b), the exo-anomeric effect is stronger in β-glycosides where there is no such competition ( 1-Oxo-β , Figure b). , On the other hand, the dihedral angle ϕ is a function of the strength of the exo-anomeric effect while ψ is influenced mainly by steric factors (Figure b). , For example, Wohlert and co-workers recently observed that 3- O -methylation of cellotetraose affects the conformational preference of those dihedral angles ϕ and ψ near the substitution point where mainly ψ shows larger shifting as a result of the steric congestion at O3 after methylation . This implies that a conformational change at the reducing end of the sugar moiety would change the dihedral angle ψ in both the α- and β-glycosides due to steric strain induced in the oxocarbenium intermediate 1-Oxo as a result of the ring flattening imposed by the double bond formed between C1 and O5.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The anomeric effect provides bolstering stability to α-glycosides due to favorable stereoelectronic and electrostatic interactions . However, due to a competition from the anomeric effect as a result of hyperconjugative lone pair electron delocalization from the endo- and exocyclic oxygen moieties in the case of α-glycosides ( 1-Oxo-α , Figure b), the exo-anomeric effect is stronger in β-glycosides where there is no such competition ( 1-Oxo-β , Figure b). , On the other hand, the dihedral angle ϕ is a function of the strength of the exo-anomeric effect while ψ is influenced mainly by steric factors (Figure b). , For example, Wohlert and co-workers recently observed that 3- O -methylation of cellotetraose affects the conformational preference of those dihedral angles ϕ and ψ near the substitution point where mainly ψ shows larger shifting as a result of the steric congestion at O3 after methylation . This implies that a conformational change at the reducing end of the sugar moiety would change the dihedral angle ψ in both the α- and β-glycosides due to steric strain induced in the oxocarbenium intermediate 1-Oxo as a result of the ring flattening imposed by the double bond formed between C1 and O5.…”
Section: Resultsmentioning
confidence: 99%
“…36,37 For example, Wohlert and co-workers recently observed that 3-O-methylation of cellotetraose affects the conformational preference of those dihedral angles ϕ and ψ near the substitution point where mainly ψ shows larger shifting as a result of the steric congestion at O3 after methylation. 66 This implies that a conformational change at the reducing end of the sugar moiety would change the dihedral angle ψ in both the αand β-glycosides due to steric strain induced in the oxocarbenium intermediate 1-Oxo as a result of the ring flattening imposed by the double bond formed between C1 and O5. Coincidentally, this change would perturb the exo-anomeric effect, thereby affecting the dihedral angle ϕ of mainly the β-glycosides.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…238 The proton and carbon resonances of this substituent are observed at characteristic δ H ∼ 3.4 and δ C ∼ 59. 239 Besides amide and ester linkages, lactic acid residues can be attached to glycans through ether bonds, and the N-acetyl muramic acid residue found in the peptidoglycan is an example of the latter (Figure 5a); in that case, the proton resonances of the lactyl group are observed at δ H ∼ 1.4 (CH 3 ) and 4.4 (CH), and the ether linkage can be recognized by the characteristic downfield chemical shift of the C2 resonance of the lactic acid moiety (δ C2 ∼ 78 ppm). 152 Interestingly, the repeating unit of the EPS from S. thermophilus contains a glucose residue that is 6-O-substituted with a nononic acid moiety through an ether linkage (Figure 5b).…”
Section: Substituents Appended To Sugarsmentioning
confidence: 99%
“…The rotamer populations of o torsion angles in hexoses with gluco/manno-configuration have a gt:gg ratio of B1 : 1 with only a small amount of the tg conformer. [108][109][110][111] The CHARMM36 and Drude force fields differ for the mannobioses in that the o 0 torsion of the terminal residue has the gt conformational state as the predominant one for CHARMM36 whereas for the Drude force field the tg conformation is significantly populated (Table 3). The population distribution for the o torsion angles in M4M derived from NMR 3 J H5,H6 coupling constants showed relative populations for the three states gt : gg : tg of 5 : 4 : 1, with only minute differences due to temperature, a phenomenon also observed in a study of hydroxymethyl rotamer populations of cello-oligosaccharides as a function of temperature over a large temperature range.…”
Section: Comparison Between Nmr Experimentally Derived and Simulation...mentioning
confidence: 99%